Factors Important to Top Clinical Performance in Emergency Medicine Residency: Results of an Ideation Survey and Delphi Panel. Issue 4 (16th August 2018) - Pines, Jesse M.; Alfaraj, Sukayna; Batra, Sonal; Carter, Caitlin; Manikoth, Nisha; Roche, Colleen N.; Scott, James; Goldman, Ellen F.
Abstract: Objectives: We explore attributes, traits, background, skills, and behavioral factors important to top clinical performance in emergency medicine (EM) residency. Methods: We used a two‐step process—an ideation survey with the Council of Emergency Medicine Residency Directors and a modified Delphi technique—to identify: 1) factors important to top performance, 2) preresidency factors that predict it, and 3) the best ways to measure it. In the Delphi, six expert educators in emergency care assessed the presence of the factors from the ideation survey results in their top clinical performers. Consensus on important factors that were exemplified in >60% of top performers were retained in three Delphi rounds as well as predictors and measures of top performance. Results: The ideation survey generated 81 responses with ideas for each factor. These were combined into 89 separate factors in seven categories: attributes, personal traits, emergency department (ED)‐specific skills and behaviors, general skill set, background, preresidency predictors, and ways to measure top performance. After three Delphi rounds, the panel achieved consensus on 20 factors important to top clinical performance. This included two attributes, seven traits, one general skill set, and 10 ED‐specific skills and behaviors. Interview performance was considered the sole important preresidency predictor and clinical competency committee results the sole important measure of top performance. Conclusion: Our expert panel identified 20 factors important to top clinical performance in EM residency. Future work is needed to further explore how individuals learn and develop these factors.